From natural induction to artificial regulation: a review on the mechanisms and techniques of flowering in pineapple - Chen, Linpan; Zhang, Miaolin; Zhang, Xiumei; Tan, Aiqi; Zhong, Fangyao; He, Junjun; Wu, Qingsong; Yao, Yanli; Li, Chuanling (Frontiers in Plant Science, 2026)
Flowering is a pivotal developmental transition in the life cycle of plants, and the precise timing of this process is crucial for successful reproduction. The flowering mechanism of the pineapple is influenced by a combination of genetic factors, environmental conditions and cultivation methods. Once pineapple plants have reached a certain number of leaves, the timing of floral bud differentiation can be regulated by applying plant growth regulators. This facilitates staggered fruit production and enables a balanced year-round supply. The timing, quantity and quality of floral bud differentiation directly affect pineapple fruit quality and yield, and also significantly impact the economic and social benefits of the pineapple industry. This paper provides a systematic review of the morphological characteristics of flowers, the patterns of floral bud differentiation, the mechanisms underlying natural and induced flowering, and the key factors influencing flowering in pineapples. This review establishes a theoretical foundation for regulating fruiting periods and optimising high-quality, high-efficiency cultivation practices.